Testing the Pecking Order Theory : Comparative Evidence between two differentiated countries (2012)
This paper analyses the financial if the behavior of the Canadian and Colombian companies follow the pecking order theory, using a sample of firms of several sectors in those countries. The study is conducted over a net sample of 74 Colombian firms and 104 Can adian firms, for the years 2006 to 2010, using the creative Shyam - Sunder and Myers (1999) model. As a general result, we observe that Canadian’s firm finance their deficit using long term debt while Colombian companies do not. Moreover other important resu lts were obtained from subdivide samples by company size.